Stereological studies of the effects of sodium benzoate or ascorbic acid on rats’ cerebellum - Noorafshan, Ali; Erfanizadeh, Mahboobeh; Karbalay-Doust, Saied (Saudi Medical Journal, 2014)
OBJECTIVES: To evaluate the cerebellar structure in sodium benzoate (NaB) or ascorbic acid (AA) treated rats.METHODS: This experimental study was conducted between May and September 2013 in the Laboratory Animal Center of Shiraz University of Medical Sciences, Shiraz, Iran. The rats received distilled either water, NaB (200mg/kg/day), AA (100mg/kg/day), or NaB+AA. The hemispheres were removed after 28 days and underwent quantitative study.RESULTS: The total volume of the cerebellar hemisphere, its cortex, intracerebellar nuclei; the total number of the Purkinje, Bergman, granule, neurons, and glial cells of the molecular layer; and neurons and glial cells of the intracerebellar nuclei reduced by 21-52% in the NaB-treated rats compared with the distilled water group (p=0.004). The total number of the Purkinje, Bergman, Golgi, and granule cells was 29-45% higher in the AA-treated rats compared with the distilled water group (p=0.05). However, these measures reduced by 17-50% in the NaB+AA-treated rats compared with the distilled water group (p=0.004). The NaB+AA group did not induce any significant structural changes in comparison with the NaB group (p>0.05). Conclusions: The NaB exposure with or without AA treatment could alter the cerebellum. Yet, AA could prevent the loss of some cells in the cerebellum.